2016
DOI: 10.21548/33-2-1121
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Antioxidant Capacity, Proanthocyanidin and Anthocyanin Content During Grape Maturation of Touriga Nacional and Tinta Roriz Grape Varieties

Abstract: To investigate antioxidant capacity in seeds and skins during grape maturation and its relationship with anthocyanin and proanthocyanidin content, two Portuguese red grape varieties, Touriga Nacional and Tinta Roriz (Vitis vinifera L.) were studied. Two analytical methods were used for antioxidant capacity analysis: the DPPH and ABTS methods. Proanthocyanidins from seeds and skins were separated into monomers, oligomers and polymers, while 13 individual anthocyanins from the skins were also evaluated by HPLC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
28
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 45 publications
7
28
0
3
Order By: Relevance
“…Our results are consistent with literature data reporting anthocyanins reach the maximum content around the harvest period [35]. Nevertheless, several works highlighted that anthocyanin concentration may slightly decrease in the last weeks of ripening or during over-maturation [6,7]. Vian et al, which studied the anthocyanin composition of Syrah grapes, observed that the maximum anthocyanin content is reached about 30 days after veraison [36].…”
Section: Individual Anthocyaninssupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are consistent with literature data reporting anthocyanins reach the maximum content around the harvest period [35]. Nevertheless, several works highlighted that anthocyanin concentration may slightly decrease in the last weeks of ripening or during over-maturation [6,7]. Vian et al, which studied the anthocyanin composition of Syrah grapes, observed that the maximum anthocyanin content is reached about 30 days after veraison [36].…”
Section: Individual Anthocyaninssupporting
confidence: 93%
“…In a general way, the antioxidant activity remained constant during grape development, having observed a significant increase from T1 to T3 only in the case of NBTCr sample. Previously, Jordão and Correia [6] observed a general decrease in both skins and seeds antioxidant activity in the early stages of maturation, followed by the stabilization of the values at the last weeks of ripening. Bordiga et al [9] evaluated the radical scavenging activity of polymeric proanthocyanidins from seeds and skins of Nebbiolo and other five grape cultivars, but did not observe any significant evolution of the antiradical values during ripening.…”
Section: Antioxidant Activitymentioning
confidence: 86%
See 2 more Smart Citations
“…Anthocyanins are the pigments responsible for the attractive colour of red wine and are one of the main flavonolic compounds with antioxidant activity, which is why red wine has a greater antioxidant activity than white wine [307][308][309][310]. Its antioxidant capacity can be up to 10 times stronger than that of white wine [205].…”
Section: Influence Of the Anthocyanins In The Antioxidant Activity Ofmentioning
confidence: 99%